Natural land subsidence in Britain: a comparative review utilising downstream InSAR data products from the EGMS and SubCoast potential subsidence map - Fountain, David (2024)
Land subsidence presents a global problem to many communities around the world, and the effects are predicted to get more substantial in the coming years due to the ensuing impacts of climate change. Although most observed land subsidence is as a result of human activities, geological deposits naturally undergo forms of subsidence without this impetus and measurements of the potential natural subsidence rates are important for planning purposes, risk management, and hazard mapping. Over the last few years there has been an increase in the availability of wide-are mapping of ground motion velocities from initiatives such as the European Ground Motion Service (EGMS). This has been made possible by the combined advances in Synthetic Aperture Radar satellite technology, sophisticated Interferometric Synthetic Aperture Radar (InSAR) processing algorithms, and the development of powerful cloud computing technologies that are capable of processing huge amounts of data.